Structural and Stratigraphic Interpretation of Zubair Formation (Lower Cretaceous) for the Area Between Halfaya, Noor, and Amara Oil Fields, Southeastern Iraq, Using 2D Seismic Reflection Data - Al-Azzawi, Bakr Samar; Ali, Kamal K. (Iraqi Journal of Science, 2025)
The study area is located in the Missan governorate in southeastern Iraq including oilfields (Halfaya, Noor, and Amara). Each field was previously studied separately, it was found that the structures were anticline folds. In this study, the three oilfields and the area between them will be studied structurally in one study to find out the extension of the structural axis of these structures within the Lower Cretaceous period, using 2D seismic reflection data. Seismic data improvement was carried out by using some attributes (structural smoothing, second derivative, phase shift, and trace AGC) to increase the visibility, accuracy, and signal-to-noise ratio. Also, the mis-tie correction was performed to match the interpretation pick at the intersection points of the seismic section. Depending on the 2D seismic reflection interpretation, and based on the well velocity survey, sonic and estimated density logs were used to make a synthetic seismogram of well Am-2. Two horizons were identified and picked (top Zubair and top Ratawi formations) within the Lower Cretaceous period. Two-way time and depth maps (3D structural model) were conducted for the picked reflectors to show the structural model of the subsurface formations. The structural interpretation shows two structural axes in the study area. The first one is the Halfaya-Amara axis whose direction is WNW-ESE corresponding with Amara structure. Due to the tectonic effect on the Halfaya structure, this axis deviates in the southeast direction. Another tectonic force affected the Halfaya structure in the NW-SE direction leading to the appearance of a branch of a convex extension towards the north from the middle of the Halfaya structure as a nose and directed towards the Noor structure. The second axis of Halfaya-Noor is in the direction of NW-SE. Application of the instantaneous phase attribute detects the sag which represents a decrease in seismic velocity in addition to a flat spot representing the seismic response of hydrocarbon-water contact, and a bright spot in the seismic section is considered a (DHI).